Assessment of Anxiolytic and Anti-depressant Activities of different Extracts of Catharanthusroseus Leaves in Experimental Animals - Shinde, Manisha; Chaudhari , Sanjay; Ritu, Gilhotra (International Journal of Psychosocial Rehabilitation, 2020)
Catharanthus roseus leaves are investigated to assess anxiolytic and antidepressant activity in experimental animal models. Successively extracted petroleum ether, chloroform, and ethanolic extracts were used in the experiment. Anxiolytic and antidepressant activity was studied using the elevated plus maze and forced swim test, respectively. Oral administration of 200 and 400 mg/kg petroleum ether extract shows significant (p<0.001) and dose-dependent anxiolytic and antidepressant activity. Diazepam 4 mg/kg, i.p., and imipramine 15 mg/kg p.o. were used as standard drugs. All the extracts at 100 mg/kg dose didn’t show significant results in the experimental animals. In qualitative chemical tests, petroleum ether extract shows the presence of tannins, flavonoids, glycosides, alkaloids, and phenolic compounds. Petroleum ether extracts are rich in phenol content, including flavonoids, which are reported responsive chemicals for anxiolytic and antidepressant activity in many preclinical studies. The assessed activities of Catharanthus roseus leaves could be due to polar and phenolic compounds.